ŹRÓDŁA PISANE I ARCHEOLOGICZNE A POSTRZEGA NIE ORGA NIZA CJI PRODUK CJI SZK ŁA RZYMSKIEGO W LITERATURZE POLSKIEJ - Krzyżanowska, Marta (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
In Polish literature, the perception of the organisation of glass production during the Roman Empire was shaped mostly in the 1980s and the 1990s. Thus the local model of glass production prevailed in these publications. In this paper, based on archaeological and written sources, the author challenges this point of view towards the centralised model of glass production widely accepted by scholars.